2016
DOI: 10.1590/1678-4324-2016150632
|View full text |Cite
|
Sign up to set email alerts
|

Application of Response Surface Methodology for Optimizing Process Parameters in the Production of Amylase by Aspergillus flavusNSH9 under Solid State Fermentation

Abstract: Amylase is recognized as one of the important commercial enzymes. This group of enzymes has the ability in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In previous studies, other researchers have tried amylase optimization using the RSM method. Roy and Mukherjee, 37 Keharom et al 38 and Stergiou et al 39 found positive effects of starch, Zambare 40 and Mustafa et al 41 found positive effects of temperature, and Gangadharan et al 42 found positive effects of CaCl 2 on amylase production using RSM method. The variables of probability p-value <0.05 were considered significant, and p-value higher than 0.05 were not considered significant.…”
Section: One Variable At a Time Approach And Plackett-burman Designmentioning
confidence: 99%
“…In previous studies, other researchers have tried amylase optimization using the RSM method. Roy and Mukherjee, 37 Keharom et al 38 and Stergiou et al 39 found positive effects of starch, Zambare 40 and Mustafa et al 41 found positive effects of temperature, and Gangadharan et al 42 found positive effects of CaCl 2 on amylase production using RSM method. The variables of probability p-value <0.05 were considered significant, and p-value higher than 0.05 were not considered significant.…”
Section: One Variable At a Time Approach And Plackett-burman Designmentioning
confidence: 99%
“…1 (continued) agitation speed, temperature and incubation period of 5, 4%, 200 rpm, 30 °C and 48 h, respectively. Mustafa et al (2016) determined the optimal fermentation conditions for maximum production of crude amylase enzyme by A. flavus NSH9 employing RSM. The maximum amylase activity was recorded as 1.055 ± 0.03 U/ml after 4 days of fermentation with 100% (v/v) moisture holding capacity, pH 6.5 and temperature 28 °C.…”
Section: Effect Of Combined Cultural Conditions On Enzyme Production mentioning
confidence: 99%
“…Previous researchers have observed similar trends in the SSF system. If the moisture level drops too low, the degree of swelling becomes low resulting in higher water tension while high moisture levels cause the porosity of the substrate to decrease, resulting in lower diffusion rates and lower gas exchange (Mustafa et al., 2016; Sondhi and Saini, 2019). The contour and surface plots revealed that the effect of the incubation time was more pronounced on tannin content.…”
Section: Resultsmentioning
confidence: 99%